IMPLEMENTASI ASESMEN BERBASIS OPEN-ENDED MATHEMATICS PROBLEMS PADA SISWA SMP YANG MENDUKUNG KURIKULUM MERDEKA [IMPLEMENTATION OF AN OPEN-ENDED BASED ASSESSMENT WITH MIDDLE SCHOOL MATHEMATICS STUDENTS THAT SUPPORTS THE MERDEKA CURRICULUM] - Mulia, Abigail Christina; Sa'dijah, Cholis; Susanto, Hery (JOHME: Journal of Holistic Mathematics Education, 2024)
Creativity is one of six basic principles required for the Merdeka Curriculum implementation. Not only is it realized through the Pancasila Student Profile Strengthening Project (P5), creativity also needs to be realized in learning activities. This research aims to describe the implementation of problem exercises based on open-ended mathematics problems as a form of formative assessment that supports the implementation of the Merdeka Curriculum, especially in supporting students' mathematical creativity. The research was conducted at SMP Negeri 5 Malang using the qualitative descriptive method. The research subjects were 32 seventh grade students in the 2023/2024 school year.The instruments used were question exercises and rubrics based on open-ended mathematics problems that have met the valid criteria, activity observation sheets, and student interview guidelines. The results showed that the assessment based on open-ended mathematics problems can assess the level of mathematical creativity and prompted the student’s mathematical creativity. In the implementation of assessment based on open-ended mathematics problems based on valid open-ended mathematics problems, data was obtained that the level of practicality of assessment reached a practicality score of 3,674 which means that assessment based on open-ended mathematics problems is easy to use. Based on the response questionnaire and interviews, further research is recommended to integrate open-ended mathematics problems-based assessment with gamification.BAHASA INDONESIA ABSTRACT: Kreativitas merupakan salah satu bentuk profil pelajar Pancasila. Tidak hanya diwujudkan melalui Proyek Penguatan Profil Pelajar Pancasila (P5), kreativitas juga perlu diwujudkan dalam kegiatan pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan implementasi latihan soal berbasis open-ended mathematics problems sebagai salah satu bentuk asesmen formatif yang mendukung pelaksanaan Kurikulum Merdeka, khususnya dalam mendukung kreativitas matematis siswa. Penelitian dilakukan di SMP Negeri 5 Malang dengan metode deskriptif kualitatif. Subjek penelitian adalah 32 siswa kelas VII tahun ajaran 2023/2024. Instrumen yang digunakan adalah latihan soal dan rubrik penilaian berbasis open-ended mathematics problems yang telah memenuhi kriteria valid, lembar observasi kegiatan, dan pedoman wawancara siswa. Pada implementasi asesmen berbasis open-ended mathematics problems yang telah valid, diperoleh data bahwa tingkat kepraktisan asesmen mencapai skor kepraktisan 3,74 yang berarti asesmen berbasis open-ended mathematics problems mudah untuk digunakan. Berdasarkan angket respons dan wawancara, penelitian lanjutan disarankan untuk mengintegrasikan asesmen berbasis open-ended mathematics problems dengan gamifikasi.